(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
The study examined the role of a prominent figure in Indonesian Islamic reform, namely Buya Hamka in Muhammadiyah from 1925 to 1966. The researchers’ interest highlighted this issue because when Muhammadiyah experienced problems, Buya Hamka came with all his efforts so that Muhammadiyah did not experience the setbacks. His role in Muhammadiyah wah significant, that between the two can not be separated from each other even the name Buya Hamka is named after a university in Jakarta. Then his determination in principle is worthy of being an example for us as the nation’s successor. The main problem of this study is about how Buya Hamka takes the role in Muhammadiyah in 1925-1966. The method used in this study is the historical method by conducting four research stages, namely heuristics, criticism, interpretation, and historiography, and the data collection techniques using literature studies. Based on the results of the study, various efforts were made by Buya Hamka in developing Muhammadiyah including establishing and teaching at Kulliyatul Muballighin, joining a team that determined the status of Muhammadiyah in Masyumi, becoming a member of the Muhammadiyah Articles of Association, and contributing to the Muhammadiyah Personality the grip of Muhammadiyah members who want to jump into politics.